Analysis of Land Deformation using Small Baseline Subset (SBAS) INSAR Technique in Pokhara, Nepal - Devkota, Pramod; Katuwal, Netra Bahadur (Journal of Engineering and Sciences, 2024)
Pokhara Valley lies in the geographic region rich in karst and the increase in urbanization with natural processes like sinkholes has led to the deformation of land causing socio-economic and physical effects on the people and the geography. Likewise, minimal research using the InSAR approach has been done in the context of the Pokhara Valley. So, this study focuses on the determination of land deformation in Pokhara Metropolitan from 2017 to 2022 using the SBAS technique. Sentinel 1A SLC images were adopted using ascending data acquisition mode. The result shows a cumulative displacement of 1578.97 mm to -1052.65 mm in ascending mode. For validation, SBAS-generated data points of the WRC regions were validated with GNSS value. The Pearson R value was found significant at a 5% significance level and the RMSD value was between 0.8 to 1.73. Thus, the results and the validation process indicate the suitability of SBAS for the determination of land displacement using SBAS.